The aphrodisiac herb Tribulus terrestris does not influence the androgen production in young men - Neychev, V.K.; Mitev, V.I. (Journal of ethnopharmacology, 2005)
The aim of the current study is to investigate the influence of Tribulus terrestris extract on androgen metabolism in young males. Twenty-one healthy young 20–36 years old men with body weight ranging from 60 to 125 kg were randomly separated into three groups—two experimental (each n = 7) and a control (placebo) one ( n = 7). The experimental groups were named TT1 and TT2 and the subjects were assigned to consume 20 and 10 mg/kg body weight per day of Tribulus terrestris extract, respectively, separated into three daily intakes for 4 weeks. Testosterone, androstenedione and luteinizing hormone levels in the serum were measured 24 h before supplementation (clear probe), and at 24, 72, 240, 408 and 576 h from the beginning of the supplementation. There was no significant difference between Tribulus terrestris supplemented groups and controls in the serum testosterone (TT1 (mean ± S.D.: 15.75 ± 1.75 nmol/l); TT2 (mean ± S.D.: 16.32 ± 1.57 nmol/l); controls (mean ± S.D.: 17.74 ± 1.09 nmol/l) ( p > 0.05)), androstenedione (TT1 (mean ± S.D.: 1.927 ± 0.126 ng/ml); TT2 (mean ± S.D.: 2.026 ± 0.256 ng/ml); controls (mean ± S.D.: 1.952 ± 0.236 ng/ml) ( p > 0.05)) or luteinizing hormone (TT1 (mean ± S.D.: 4.662 ± 0.274 U/l); TT2 (mean ± S.D.: 4.103 ± 0.869 U/l); controls (mean ± S.D.: 4.170 ± 0.406 U/l) ( p > 0.05)) levels. All results were within the normal range. The findings in the current study anticipate that Tribulus terrestris steroid saponins possess neither direct nor indirect androgen-increasing properties. The study will be extended in the clarifying the probable mode of action of Tribulus terrestris steroid saponins.